2015
DOI: 10.1093/ijnp/pyv124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose and Very Low-Dose Ketamine among Patients with Major Depression: a Systematic Review and Meta-Analysis

Abstract: Background:Several recent trials indicate low-dose ketamine produces rapid antidepressant effects. However, uncertainty remains in several areas: dose response, consistency across patient groups, effects on suicidality, and possible biases arising from crossover trials.Methods:A systematic search was conducted for relevant randomized trials in Medline, Embase, and PsycINFO databases up to August 2014. The primary endpoints were change in depression scale scores at days 1, 3 and 7, remission, response, suicidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 39 publications
13
137
0
3
Order By: Relevance
“…[41] These results suggest that the antidepressive effects of ketamine may be dose-related. The antidepressive effects of four IV doses of ketamine (0.1, 0.2, 0.3, and 0.4 mg/kg infused over 2-5 min) were tested in a small, double-blind, placebo-controlled cross-over pilot study of four depressed subjects, using an ascending dose design.…”
Section: Lack Of Established Dose Range or Dose-response Relationshipmentioning
confidence: 92%
See 1 more Smart Citation
“…[41] These results suggest that the antidepressive effects of ketamine may be dose-related. The antidepressive effects of four IV doses of ketamine (0.1, 0.2, 0.3, and 0.4 mg/kg infused over 2-5 min) were tested in a small, double-blind, placebo-controlled cross-over pilot study of four depressed subjects, using an ascending dose design.…”
Section: Lack Of Established Dose Range or Dose-response Relationshipmentioning
confidence: 92%
“…3 (number needed to treat). A separate meta-analysis by Xu et al [41] also reported large effects favoring ketamine for short-term positive response (pooled response rate 50 vs. 13%, RR 2.6, 95% CI: 1.6-4.4 at 24 hrs; pooled response rate 31 vs. 7%, RR 3.4, 95% CI: 1.6-7.1 at 7 days), and remission (pooled remission rate 28 vs. 3%, RR 5.2, 95% CI: 2.1-12.9 at 24 hrs; pooled remission rates 24 vs. 6%, RR 2.6, 95% CI: 1.2-5.7 at 7 days) [42] Total (n = [43] Total (n = Xu et al 2015 [41] Total (n = Lee et al 2015 [44] Total (n = Romeo et al 2015 [45] Total (n = Coyle and Laws [46] Total (n = [47] Total (n = Fond et al 2014 [48] Total (n = Caddy et al 2014 [49] Total (n = The study sample in one reviewed study consisted of depressed patients presenting acutely to an emergency room with suicidal ideation.…”
Section: Review Of the Evidence Rapid But Variable And Short-lived Anmentioning
confidence: 99%
“…The dose of ketamine used in this study was derived from studies in which ketamine infusions have been shown to be effective in the rapid treatment of depression 165 and, therefore, it is possible that a different dose of ketamine may have shown benefit in terms of cognitive, or possibly efficacy, outcomes. However, as discussed in the previous paragraph, it is likely that higher doses would be associated with a less favourable AE profile (see also McGirr et al…”
Section: Neuropsychological Outcomesmentioning
confidence: 99%
“…) and the data from studies using higher doses of ketamine with ECT, 52 or as a pharmacological treatment, 165 do not suggest an efficacy benefit.…”
mentioning
confidence: 97%
“…However, there is substantial heterogeneity in clinical response, and ketamine's underlying mechanisms of action are not entirely understood. 14,15 The observation that a single intravenous dose of glutamatergic modulator ketamine produces a robust and rapid AD effect was a turning point that opened the way for other, more selective glutamatergic modulators (intranasal esketamine, rapastinel). 16 …”
Section: Ketaminementioning
confidence: 99%